Life Support in the Arctic Upon Synchronizing the Development of the Northern Territories of Yakutia - Galia E. Kokieva1 , Anna G. Cherkashina2 , Motrena N. Khaldeeva3, Galina A. Gerasimova4 , Nadezhda K (Indian Journal of Forensic Medicine & Toxicology, 2020)
The role of the Arctic and Northern regions, especially the Republic of Sakha (Yakutia) in the geopolitical position of Russia in the world is increasing every day. The purpose of the study is to investigate the branches of life support in the Arctic upon synchronizing their development. The leading research method for this problem is the analysis method. The paper describes innovative ways to manage the life support sectors in the Arctic upon synchronizing their development, restructuring and reforming. The comparison of the Strategy for the development of a unified energy system of the Republic of Sakha until 2030 and the Republican target program is provided. The novelty of the study is determined by the fact that it analysed the urgent problem of the need to separate the management system by industry, by creating branch ministries corresponding to the structure of the Government of the Russian Federation. The practical significance of the study is determined by the need to expand and implement the existing program of targeted training, to ensure close communication between the enterprises of fuel and energy complex and educational institutions of the Republic.